Distinctive Multipath Based Data Chunk Sequencing Scheme (International Journal of Engineering and Computer Science, 2014)
A Mobile network is a hybrid network on which the different kind of data is communicated. One of the critical communicating data type over network is video transmission. Video Transmission with high resolution increases the network traffic that can result the packet loss over the network. The criticality of the situation is increased when the network is also suffering from some attack or the heavy load over the network that performs the flooding so that that the networks delay is increased over the network. In this paper, a distinctive multipath based data chunk sequencing scheme is suggested to perform the reliable communication over the clustered mobile network.